Beyond good and evil : prelude to a philosophy of the future - Nietzsche, Friedrich Wilhelm, 1844-1900.; Zimmern, Helen, 1846-1934 (London & Edinburgh, T. N. Foulis, 1909)
Beyond Good And Evil asks, is truth absolute? Do humans invent ways to fortify already held views or truly seek the truth? Are the powerful more 'right' than the weak? Or is Nietzsche writing down page after page to hear himself talk?
Keywords: Ethics; Good and evil; Philosophy, German -- 19th century; Morale